2020
DOI: 10.1038/s41467-020-15724-9
|View full text |Cite
|
Sign up to set email alerts
|

Fermionic neural-network states for ab-initio electronic structure

Abstract: Neural-network quantum states have been successfully used to study a variety of lattice and continuous-space problems. Despite a great deal of general methodological developments, representing fermionic matter is however still early research activity. Here we present an extension of neural-network quantum states to model interacting fermionic problems. Borrowing techniques from quantum simulation, we directly map fermionic degrees of freedom to spin ones, and then use neural-network quantum states to perform e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
195
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 43 publications
2
195
0
Order By: Relevance
“…Nagai et al 8 showed that accurate densities of just three small molecules are sufficient to create machine-learned approximations that are comparable to those created by people. In ab initio quantum chemistry, Welborn et al 9 have shown how to use features from Hartree-Fock calculations to accurately predict CCSD energies, while an intriguing alternative is to map to spin problems and use a restricted Boltzmann machine 10 . In the last year, two new applications for finding wavefunctions within QMC have appeared 11,12 .…”
mentioning
confidence: 99%
“…Nagai et al 8 showed that accurate densities of just three small molecules are sufficient to create machine-learned approximations that are comparable to those created by people. In ab initio quantum chemistry, Welborn et al 9 have shown how to use features from Hartree-Fock calculations to accurately predict CCSD energies, while an intriguing alternative is to map to spin problems and use a restricted Boltzmann machine 10 . In the last year, two new applications for finding wavefunctions within QMC have appeared 11,12 .…”
mentioning
confidence: 99%
“…To enhance the computational efficiency of the RBM, the QRBM model are proposed [11,12,13]. Different from the RBM, the QRBM utilizes a quantum circuit to parallelly compute the amplitudes Ψ v (θ), and naturally outputs the superposition state |Ψ(θ)…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [12] proposed a variational quantum algorithm to efficiently train the QRBM, where the proposed algorithm reduced the required ancillary qubits. Recently, Carleo et al [13] presented an extension of quantum neural network to model interacting fermionic problems, and Kerstin et al [22] indicated that the Deep QRBM can implement the universal quantum computation tasks. The previous works show outstanding performance in some notable cases of physical interest that are difficult for classical RBM.…”
mentioning
confidence: 99%
“…In this section we look at the time evolution of Hamiltonians arising from fermionic many-body quantum systems. We use the spin Hamiltonians obtained in [14] by using the second quantization formalism of the fermionic system followed by a conversion to interacting spin models by applying the Jordan-Wigner, Bravyi-Kitaev, or parity encodings [11,23]. The resulting Hamiltonians are expressed as a weighted set of Paulis, as desired.…”
Section: Quantum Chemistrymentioning
confidence: 99%